The Antecedents of Purchase Decision at Online Travel Agent (Tiket.com) - Lila Maria Kaban; Leonardo Stevanus (PT Mattawang Mediatama Solution, 2023)
An online travel agent is one of the platforms that has evolved throughout this digital era, including Tiket.com. Unfortunately, when the Covid-19 pandemic hit, online travel agents were affected the most. Now it is time for Tiket.com to evaluate its marketing strategies to increase the customers' purchase decisions. This research aims to analyze which strategies among Perceived Trust, E-Service Quality, Online Rating, and Online Review have the biggest influence on customer’s Purchase Decision on Tiket.com. This study is conducted from September to December 2022, using a quantitative method with purposive sampling by distributing an online questionnaire to 50 customers of Tiket.com. The data is analyzed for multiple regression analysis to find the influence of each independent variable on the dependent variable. Results show that E-Service Quality, Online Rating, and Online Review have a positive and significant influence on Purchase Decision while Perceived Trust has a positive but insignificant influence on Purchase Decision. Further, Online Rating is found to have the biggest influence on Purchase Decision. Thus, it is important for Tiket.com to pay attention to its Online Rating and Review, E-service Quality, and Perceived Trust.